The effect of cervical length on procedure time and VAS pain score in office hysteroscopy - Cenk Soysal; Onur Ince; Yasemin Taşçı (Scientific Reports)
Abstract This study aimed to investigate the effect of cervical length on procedure time and VAS pain scores during office hysteroscopy. A cross-sectional study was conducted on 50 patients who underwent office hysteroscopy for various indications such as abnormal uterine bleeding and infertility. Exclusion criteria included active vaginal infection, previous cervical surgery, and chronic pelvic pain. Cervical length was measured via transvaginal ultrasound prior to the procedure. Procedure time and VAS pain scores were recorded and analyzed. Patients with a retroverted uterus had higher post-procedure VAS scores (7.6 ± 0.8) compared to those with an anteverted uterus (4.9 ± 1.9, p < 0.001). Cervical length was found to be a significant predictor of both procedure time (β = 5.711, p < 0.001) and VAS pain score change (β = 0.167, p < 0.001). Procedure time was significantly longer in patients with increased cervical length (R2 = 79.6%, p < 0.001). Additionally, an anteverted uterus was associated with a shorter procedure time (118.2 ± 49.2 s) compared to a retroverted uterus (142.7 ± 46.8 s, p < 0.001). Cervical length was a significant predictor of VAS pain scores (β = 0.167, p < 0.001), with each millimeter increase leading to a 0.167-unit rise. While univariate analysis showed a negative association between age and VAS scores (β = -0.299, p = 0.035), this was not significant in the multivariate model (p = 0.586). Cervical length also significantly prolonged procedure time (β = 5.711, R2 = 79.6%, p < 0.001). Cervical length is a significant factor influencing both the duration and pain experienced during office hysteroscopy. Consideration of cervical length can improve patient comfort and procedural efficiency in clinical practice.